Teaching a CS introductory course : an active approach - Moura, Isabel Cristina A. A. (2011)
Computer Science (CS) introductory courses that are offered by the Department of Information Systems at the University of Minho (UM), Portugal, seem to abound in non-motivated students. They are characterized by high failure and withdrawal rates and use mainly deductive teaching approaches. Deductive instruction begins with theories and progresses to applications of those theories. Active approaches to teaching are more inductive. Inductive instruction begins with the presentation of, for instance, a specific problem that introduces a topic, and theories are studied on a need-to-know basis. This pilot study describes how active learning techniques have been successfully applied to a CS introductory course, reducing its failure and withdrawal rates. The study portrays the changes in the course from teachercentered education to a learner-centered approach, using two different editions of the same course, the first one being teacher-centered and the second learner-centered. The results in terms of success, failure, and dropout are given and the impact of a more student-centered approach on student involvement in learning is analyzed. The authors discuss implications of student-centered learning for the classroom and pay attention to some of the drawbacks of an implementation more focused on active learning.